A cluster randomised trial of educational interventions to promote rational prescribing in primary care - Naughton, Corina (Trinity College (Dublin, Ireland). School of Medicine. Discipline of Pharmacology & Therapeutics, 2008)
A randomised controlled trial (RCT) was used to evaluate the effectiveness of individualised GP prescribing feedback delivered as a postal bulletin (PB, n=50 practices) compared to PB plus academic detailing visits (AD, n=48 practices), in promoting ratbnal prescribing among a volunteer group of Irish GPs. The background changes in prescribing were examined using a quasi-experimental design, where prescribing practice from participant GPs (n=110) was compared to those GPs who declined to participant in the study i.e. non-participant GPs (NP, n=190). The aims of the interventions were to: (1) reduce the rate of overall antibiotic prescribing, (2) reduce second line antibiotic prescribing (co- amoxiclav & cephalosporins), (3) promote generic substitution for five targeted drugs and (4) increase prescribing of preventive therapies i.e. antiplatelet, statins and antihypertensive therapy in patients with established cardiovascular disease (CVD) or diabetes. The interventions consisted of two separate postal bulletins with the associated academic detailing visits over a six month period (March 2005 to August 2005). The academic detailing visits consisted of a ten minute powerpoint presentation reiterating the message in the postal bulletin and discussion with the GP.
Keywords: Pharmacology Pharmacy, Ph.D.; Ph.D. Trinity College Dublin